Resistance to Powdery Mildew in Qingke Involves the Accumulation of Aromatic Phenolamides Through Jasmonate-Mediated Activation of Defense-Related Genes - Xu, Congping; Zhan, Chuansong; Huang, Sishu; Xu, Qijun; Tang, Tang; Wang, Yulin; Luo, Jie; Zeng, Xingquan (Frontiers in Plant Science, 2022)
Powdery mildew (PM) leads to severe yield reduction in qingke. Although studies have focused on identifying PM-related resistance genes, mechanistic insights into the metabolic regulation networks of resistance against PM have rarely been explored in qingke. Here, we integrated transcriptomic, proteomic and metabolomic data using PM-sensitive (G72) and PM-resistant (K69) accessions to systemically explore the mechanisms of PM resistance. The results show that a rapid accumulation of jasmonic acid (JA) and (+)-7-iso-jasmonoyl-L-isoleucine (JA-Ile) and, importantly, an induced accumulation of aromatic phenolamides (PAs) conferred species-specific resistance against PM. Furthermore, chromatin immunoprecipitation (ChIP)-seq assays revealed that H3K27me3 levels of HvTBT1 and HvTBT2, which are responsible for the synthesis of aromatic PAs, were significantly reduced in methyl jasmonate (MeJA)- and PM-treated plants. Overall, our results suggest a potential strategy for JA signal-mediated demethylation that controls the accumulation of aromatic PAs that contribute to plant immune resistance through the activation of defence-related gene expression.